Personality traits and consumer acceptance of controversial food technology: A cross-country investigation of genetically modified animal products. (September 2019) - Lin, Wen; Ortega, David L.; Caputo, Vincenzina; Lusk, Jayson L.
Highlights: Personality traits influence preferences for genetically modified animal products. Openness increased consumer acceptance in the US, China and Italy. Conscientiousness decreased acceptance in Western consumers. Personality traits can be used for market segmentation to improve product viability. Abstract: Recent breakthroughs in biotechnology have expanded the range of applications in animal agriculture. Acceptance of food products from these animals is expected to be controversial and requires a thorough understanding of consumer preferences and drivers of acceptance. This paper explores the role of personality, measured via the Big Six personality traits ( Agency, Agreeableness, Openness, Neuroticism, Extraversion and Conscientiousness ), on consumer acceptance of a genetically modified pork product in the US ( N  = 945), China ( N  = 945) and Italy ( N  = 954). The effect of personality is most evident in US consumers with five out of six personality traits explaining preferences for genetically modified pork. Openness was the only trait that consistently explained consumer acceptance in our three countries and conscientiousness was found to be a good predictor in Western cultures. Our results reinforce the need to use psychological characteristics of consumers to understand controversial food acceptance and highlight the differential impact of personality across cultures.